Micro-Assembly Technologies and Applications
DOI: 10.1007/978-0-387-77405-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Precision Assembly of Active Microsystems with a Size-Adapted Assembly System

Abstract: The paper presents a size-adapted assembly system for the automated precision assembly of active microsystems. The part sizes of the microsystems can reach centimeter range, but they must be assembled with an assembly accuracy of about a few micrometers. The results of a sensor guided assembly process using a 3D vision sensor are shown. This process reaches a positioning uncertainty of 1.2 \xm and an assembly uncertainty of 36 urn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Further, the more that is seen of the part, the more accurately it can be placed using a vision based relative position system. This was shown in [2], in which a large assembly error is attributed to limited visibility of the part during the relative positioning phase. It is shown that the assembly error of the finished part was drastically larger on the side of the part which was covered by the gripper.…”
Section: Increasing Part Visibilitymentioning
confidence: 87%
See 2 more Smart Citations
“…Further, the more that is seen of the part, the more accurately it can be placed using a vision based relative position system. This was shown in [2], in which a large assembly error is attributed to limited visibility of the part during the relative positioning phase. It is shown that the assembly error of the finished part was drastically larger on the side of the part which was covered by the gripper.…”
Section: Increasing Part Visibilitymentioning
confidence: 87%
“…To recall the assembly data which was obtained through the assembly of 33 guide/stator groups and the older vacuum gripper, a positioning uncertainty of 1.2 micrometers and an assembly uncertainty of 36 micrometers were thus obtained [2]. The resulting assembly uncertainty along with the data can be seen on the left hand side of figure 5.…”
Section: Increasing Part Visibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the dimension of the handled parts and the philosophy of size adapted handling systems [2] the gripping system should not be bigger than 3 cm in all directions. The used Peltier element has a dimension of 16x16 mm² and a power of 34 W. With heat sink, isolation, sensors and connection parts the whole dimension of the gripper is 35x15x30 mm³.…”
Section: Active Gripper Systemmentioning
confidence: 99%
“…To reach this goal, many endeavors in the field of high accurate handling and positioning systems were and are made [2,3,4]. Another very important part is the use of a suitable bonding technology.…”
Section: Introductionmentioning
confidence: 99%